Pengembangan Model Latihan Passing Dan Movement Without The Ball Futsal Pada Kegiatan Ekstrakulikuler Sekolah Menengah Atas Berbasis Games Kompetisi - Idris, Fahmi; Febi Kurniawan; Akhmad Dimyati (Program Studi Pendidikan Kepelatihan Olahraga Fakultas Ilmu Pendidikan Universitas Bhayangkara Jakarta Raya, 2020)
This research describes the development of a passing & movement without the ball training model in futsal games. In this study, researchers collaborated with 3 (three) experts in the field of futsal. Through validation tests conducted using expert justification tests, this study resulted in 15 (fifteen) item models of passing and movement without the ball training in futsal games. The purpose of this study is to be used as reference material for coaches in providing futsal training models. This research was conducted at SMA Negri 1 Telukjambe by taking participants who took part in futsal extracurricular activities. To answer the formulation of research problems that had been formulated, the writing used a descriptive qualitative approach with the research and development (R&D) method. The subjects in this study were 23 (twenty three) members of the extracurricular participants in two high schools.